Antioxidant ativities of wine spirits aged by a sustainable technology using chestnut wood staves and micro-oxygenation - Oliveira-Alves, S. (2022)
Antioxidant ativities of wine spirits aged by a sustainable technology using chestnut wood staves and micro-oxygenation.